Empowering Rural Communities: A Theoretical Approach to Sustainable Tourism through Community-Based Development - Rico Susana Restrepo; Peterek Michael (Technical Transactions)
Sustainable tourism is an important element in the policies of many developing countries today. In contrast to mass tourism, it provides a holistic perspective, recognising the synergies between economic, social, and environmental development and protecting the existing natural, human and organisational resources upon which tourism depends. Community-based tourism (CBT) is a participatory approach to implementing sustainable tourism that also promotes community development from a bottom-up perspective and with a focus on local knowledge and existing resources. Based on comprehensive research and analysis of the existing body of literature, the aim of this paper is to research the transition from sustainable tourism towards community based-tourism, to identify the relevant actors that should be involved in the planning, implementation and management of such projects and to propose a capacity development approach that facilitates community development through a community-based tourism approach.